TERMINOGRAPHY AS A SCIENTIFIC SCIENCE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Terms are essential part of all languages, so leaning them as a separate subject is vitally important. Taking it into account, the purpose of the article is to research on terminology as a scientific science. Moreover, the article illustrates some features of terminology in modern linguistics.